AB0801 Skin scores of patients with systemic sclerosis correlate with circulating thyrotropin levels. (23rd January 2014) - Bagnato, G.; Roberts, W.N.; Sangari, D.; Atteritano, M.; Talotta, R.; Miceli, G.; Bagnato, G.
Abstract : Background: Hypothyroidism has a higher prevalence in systemic sclerosis (SSc) patients 1 and thyrotropin (TSH) receptor is widely expressed in human tissues 2, included the skin 3 and the aorta 4 . Objectives: Our aim, therefore, was to measure skin scores across the clinical spectrum of limited and diffuse scleroderma and to correlate these scores with serum TSH levels. Methods: In a cross-sectional study we compared skin severity modifiedRodnan total skin scores (TSS) to circulating TSH levels in 43 patients with scleroderma (18 with diffuse form, 25 with limited form). SSc patients with hypothyroidism necessitating thyroid hormonal replacement therapy and patients with positive TSH receptor antibodies were not enrolled. We also concurrently measured free triiodothyronine (FT3), free thyroxine (FT4), TSH receptor antibodies (TRAb), anti-thyroid peroxidise (TPOAb) and anti-thyroglobulin (TgAb), all by chemiluminescence immunoassay. Results: Enrolled patients were all female with a mean age of patients was 50.04±13.07 years and a mean disease duration was 7.9±6 years. Skin scores for the entire group averaged 9.40±5.05, while the mean TSH was 2.05±1.14. Spearman's rank correlation between the TSS and TSH was statistically significant (r=0.75, p<0.0001). Other thyroid hormonal measurements and anti-thyroid antibodies correlated poorly with skin scores. Conclusions: TSH is higher for patients with more severe skin disease. Therefore TSH could play a role in the development of cutaneous fibrotic changes in SSc patients. Further confirmatory analyses are needed to establish the role of thyrotropin in systemic sclerosis pathogenesis. References: Antonelli A, et al. Clinical and subclinical autoimmune thyroid disorders in systemic sclerosis. Eur J Endocrinol. 2007 Apr; 156(4)431-7. Klein, JR. Physiological relevance of thyroid stimulating hormone and thyroid stimulating hormone receptor in tissues other than the thyroid. Autoimmunity. 2003 Sept-Nov;36(6-7):417–421. Cianfarani F, et al. TSH receptor and thyroid-specific gene expression in human skin. J Invest Dermatol. 2010 Jan;130(1):93-101. Donnini D et al F. Thyrotropin stimulates production of procoagulant and vasodilative factors in human aortic endothelial cells. Thyroid. 2003 June;13(6): 517-21 Disclosure of Interest: None Declared